AN ANALYTICAL STUDY OF EDUCATIONAL RIGHTS OF WOMEN IN ISLAM - Dr. Hafiz Mudassar Shafique; Dr. Zubair Tayyab; Dr. M. Talha Hussain; Muhammad Aminuddin; Dr. Anwarullah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Rights refer to the benefits and demands enjoyed by mankind from which they cannot be deprived. In case of deprivation, they can be recovered by legal action because the creator and owner of this universe had entrusted the human being with their basic rights at the time of their birth. Undoubtedly, these rights are granted by nature but when we turn the pages of history, the developed or undeveloped civilizations of the world religions have always violated the rights of women. Woman, who is half of this universe and the guardian of generations and it has always been a victim of social oppression. The system of relationships in this universe is based on the union of man and woman. The system of life offered by Islamic Shariat is based on equality between men and women. Islam does not believe in any discrimination between men and women, but requires that men and women fulfill their rights and duties in a good manner. Islam advocates justice in rights. In the religion of Islam, woman has been declared as the main pillar of the society. Women’s rights have not been reduced in any way, just like men’s rights are women’s rights. Whether these rights are related to education or any other aspect of life. Islam provides complete guidance for men and women in all these aspects. Islam is the only religion which gave women all the rights fourteen hundred years ago for which women are fighting today. Before Islam and after Islam, the non-Muslim woman was not given the status she deserved. With the emergence of Islam, Islam gave women their economic, social, educational, legal, inheritance and all other rights which were suspended by all the nations of the world.